Good faith in the jurisprudence of the WTO : the protection of legitimate expectations, good faith interpretation, and fair dispute settlement - Panizzon, Marion (Studies in international trade law, 2006)
What does the concept of good faith express? This book is the first to discuss what good faith means in international trade law. As a reference guide for scholars and practitioners it analyses the case law of WTO dispute settlement practice. The book describes how, why and when the concept of good faith links the WTO Agreements with other public international norms. The concept of good faith appears frequently in treaties and customary rules, but is most often considered a general principle of law. WTO law uses the corrolaries of pacta sunt servanda, the prohibition of abus de droit and the pr.